CONCEPTUAL ANALYSIS OF COGNITIVE METAPHORS EXPRESSING HUMAN INNER PSYCHOLOGY (European Journal of Interdisciplinary Research and Development, 2025)
This paper explores the conceptual analysis of cognitive metaphors as a means of representing human inner psychology in language. Metaphor is not merely a stylistic device, but a fundamental cognitive mechanism that allows abstract mental states to be verbalized through concrete linguistic forms (Lakoff & Johnson, 1980). By examining linguistic data from English and Uzbek, this study demonstrates how metaphors construct and reflect the inner psychological world, including emotions, desires, and cognitive processes. The aim of the research is to investigate how inner psychological phenomena are encoded in metaphorical models and how these models function as universal yet culturally shaped tools of expression. The findings show that metaphors play a dual role: they both externalize inner experiences and serve as cultural frameworks for conceptualizing human psychology